ANALISIS YURIDIS PELAKSANAAN PROGRAM PROYEK OPERASI NASIONAL AGRARIA (PRONA) SEBAGAI UPAYA PEMERINTAH TERHADAP PERCEPATAN PENDAFTARAN TANAH DI DAERAH, STUDI PADA KANTOR PERTANAHAN KOTA PADANGSIDIMPUAN - AHMAD HUSEIN PAN HARAHAP (PREMISE LAW JURNAL, 2017)
Since 1974 the government has done the two ways, and around 2000s the government has subsidized them by using PRONA (National Agrarian Program) by giving mass certificates and strategic land dispute settlemen. The research problems are as follows: how about the implementation of PRONA in the working area of the Land Office of Padangsidimpuan, the use of PRONA, and how about the obstacles and the effort to settle them by the Land Office of Padangsidimpuan in implementing PRONA in its working area. The implementation of PRONA in Padangsidimpuan is done gradually. PRONA facilitates people to have their land certificates with simple process and the cost is guaranteed by the government. People are facilitated by the government from the process until the cost of certification. Some obstacles in land registration through PRONA are people ignorance of the regulation and their misunderstanding in its cost. It can be settled by providing counseling about its implementation with guidance and procedure of PRONA. Keywords: Land Registration, PRONA, National Land Agency